Lifetime recreational moderate‐to‐vigorous physical activity and ovarian cancer risk: A case–control study. Issue 7 (1st July 2019) - Grundy, Anne; Ho, Vikki; Abrahamowicz, Michal; Parent, Marie‐Élise; Siemiatycki, Jack; Arseneau, Jocelyne; Gilbert, Lucy; Gotlieb, Walter H.; Provencher, Diane M.; Koushik, Anita
Abstract : Results of epidemiologic studies of physical activity and ovarian cancer risk are inconsistent. Few have attempted to measure physical activity over the lifetime or in specific age windows, which may better capture etiologically relevant exposures. We examined participation in moderate‐to‐vigorous recreational physical activity (MVPA) in relation to ovarian cancer risk. In a population‐based case–control study conducted in Montreal, Canada from 2011 to 2016 (485 cases and 887 controls), information was collected on lifetime participation in various recreational physical activities, which was used to estimate MVPA for each participant. MVPA was represented as average energy expenditure over the lifetime and in specific age‐periods in units of metabolic equivalents (METs)‐hours per week. Odds ratios (OR) and 95% confidence intervals (CI) for the relation between average MVPA and ovarian cancer risk were estimated using multivariable logistic regression models. Confounding was assessed using directed acyclic graphs combined with a change‐in‐estimate approach. The adjusted OR (95% CI) for each 28.5 MET‐hr/week increment of lifetime recreational MVPA was 1.11 (0.99–1.24) for ovarian cancer overall. ORs for individual age‐periods were weaker. When examined by menopausal status, the OR (95% CI) for lifetime MVPA was 1.21 (1.00–1.45) for those diagnosed before menopause and 1.04 (0.89–1.21) for those diagnosed postmenopausally. The suggestive positive associations were stronger for invasive ovarian cancers and more specifically for high‐grade serous carcinomas. These results do not support a reduced ovarian cancer risk associated with MVPA. Abstract : What's new? While physical activity is associated with a reduced risk of certain cancer types, its relationship with ovarian cancer risk remains unclear. In this population‐based case–control study in Montreal, Canada, participation in recreational physical activities over the lifetime and in specific life periods was examined in relation to ovarian cancer risk. Analyses did not find that moderate‐to‐vigorous physical activity was associated with a reduced ovarian cancer risk. Rather, the data hinted toward a marginal increase in risk, which was more apparent particularly among women diagnosed with ovarian cancer before menopause and women with high‐grade serous tumors.